B-Li-Cl Trend Line Can Distinguish The Dominance of Hydrothermal Water and Surface Water: A Case Study of Geothermal in Tengchong, Southwestern China - Feng-Yun Huang; Shakal Khan Korai (International Journal of Hydrological and Environmental for Sustainability, 2025)
The Boron-Lithium-Chlorine (B-Li-Cl) trend line serves as a valuable geochemical tool for distinguishing the dominance of hydrothermal water and surface water in geothermal environments. In this study, we applied the B-Li-Cl trend line to analyze the geochemical characteristics of water samples from the Tengchong geothermal area in Southwestern China. Our results reveal distinct patterns that differentiate hydrothermal water from surface water, offering insights into the geochemical processes and interactions occurring in this region. The lower Cl/Li and Cl/B ratio values of meteoric water with a Cl concentration of <10 (mg/L) indicate that mixing occurs not only when migrating upwards, but also inwards. The absence of a trend formed at a Cl concentration of <10 (mg/L) proves that the Cl concentration can be diluted by mixing with meteoric water. Meanwhile, the concentrations of Li > 100 (µg/L) and B > 1 (mg/L) form a downward trend from magmatic water, while the concentration of B < 1 (mg/L) has a downward trend from meteoric water. Both interpretations confirm that the behaviour of Lithium and Boron towards temperature changes has the same tendency, which can illustrate the origin of hydrothermal water formation.